Effect of Financial Distress on Going Concern Audit Opinion - Bellinda Cindy Audry; Dyah Mieta Setyawati (Formosa Journal of Science and Technology, 2023)
This study aims to determine the effect of financial distress and the previous year's audit opinion on going concern audit opinion. The analysis technique used is the modified Altman method and logistic regression analysis with the help of SPSS version 22. The results of the analysis show that financial distress affects going-concern audit opinion, this means that if financial distress is determined by the lower the Z value, the higher the probability the company received a going concern audit opinion. The previous year's audit opinion has an effect on going concern audit opinion, this shows that if a company gets a going concern audit opinion in the previous year, it will be more likely for the company to receive a going concern audit opinion again in the current year. And the overall results show that financial distress and the previous year's audit opinion have a joint effect on the going concern audit opinion.